Dynamic mechanical properties of oil palm nano filler/kenaf/epoxy hybrid nanocomposites. (15th October 2016) - Saba, N.; Paridah, M.T.; Abdan, K.; Ibrahim, N.A.
Highlights: Effect of oil palm nano filler on DMA of epoxy hybrid nanocomposites were made. Tg and shapes of cole-cole plot of kenaf/epoxy and hybrid nanocomposites evaluated. Comparative DMA study of oil palm nano filler, MMT and OMMT hybrid nanocomposites. Considerable improvement in dynamic properties observed for nano OPEFB hybrid. Abstract: Epoxy based hybrid nanocomposites was prepared by dispersing the different nano fillers -nano oil palm empty fruit bunch (OPEFB) filler, MMT, and OMMT at 3% loading through high speed mechanical stirrer followed by hand lay-up technique. Dynamic mechanical analysis (DMA), in terms of storage modulus (E′), loss modulus (E″), Tan delta ( δ ) and glass transition temperature (Tg) as a function of temperature were carried out. Overall results indicated that E′, E″ and Tg increased considerably by incorporating nano OPEFB filler, MMT and OMMT nanoclay into the kenaf/epoxy composites. Nano OPEFB/kenaf/epoxy hybrid nanocomposites displayed comparable properties to MMT/kenaf/epoxy but less than OMMT/kenaf/epoxy hybrid nanocomposites.